Peasant resistance and the colonial encounter in Sri Lanka in the Seventeenth and Eighteenth centuries - Dewasiri, N.R. (University of Colombo, 2017)
The nature of the European colonial encounter, the ways in which indigenous people responded to the colonial presence, and the specific nature of the polity that emerged out of the colonial domination are still debated by scholars. This paper seeks to address these issues by looking at the peasant revolts in Southern Sri Lanka in the context of the Portuguese and the Dutch interventions. The research problem concerns the question of how to understand these revolts or peasant uprisings as the dominant mode of explanation envelops them in the general narrative of anti-colonial struggles. The method is critical reading of contemporary and near-contemporary records, both published and archived, and of the modern scholarly discourses of the anti-colonial struggles. The conceptual framework is mainly drawn from the works of Irfan Habib, Ranajith Guha and others. The 1616 revolt was reportedly led by Nikapitiye Bandara and Kuruvita Rala, who were outsiders to the traditional ruling elite. Their ability to mobilize peasants was enhanced by the weakened hegemonic links between the Portuguese and the peasantry. Riots in the Dutch territory in the early eighteenth century were caused by measures taken by the Dutch to raise the level of surplus extraction. These revolts signalled the break-up of the traditional system of authority. These revolts were alarming, not only for the colonial powers but also, at times, for the indigenous ruling elite as well. The Dutch were able to devise new forms of governmentalisation in order to re-hegemonise the peasantry, which was a sine qua non for the maximization of the extraction of the surplus of the peasant.
Keywords: colonial domination, Dutch rule in Sri Lanka, Portuguese rule in Sri Lanka, peasant, surplus extraction